CHARACTERISATION OF A MOBILE JAW CRUSHER FOR SMALL SCALE MINING AND CONSTRUCTION INDUSTRY - Itika, A. J. M. (Tanzania Journal of Engineering and Technology, 2018)
A small jaw crusher with a crushing capacity of 1 ton per hour has been developed for use in the small scale mining and construction industry. A 3.68 kW air cooled diesel engine was installed to power the crusher. Laboratory and field test were conducted using limestone as feed material at different operating parameters. The analysis of the product from the crusher showed that at a constant jaw gap, coarser products were obtained when the rotary speed was varied from 220 rpm to 300 rpm. With a jaw gap of 25 mm, a higher cumulative undersize fraction was obtained at particle size 25 mm. In contrast, at a jaw gap of 15 mm, higher cumulative undersize fraction was obtained at particle size 15 mm. With a feed size 80% passing 60 mm, a finer product was obtained as compared to a feed 80% passing 120 mm. The throughput of the machine increased from 0.4 ton/hr to 0.7 ton/hr when the speed was increased from 220 rpm to 300 rpm. It was found that it is possible to select a combination of operating parameters to achieve a particular goal of operation.